👤

Descompuneti in factori :
1) x la 2 - 5x =
2) 3x la 10 + 9x la 8 =
3) x(x + 1) - x - 1 =
4) x la 2 (x+1) + x (x+1) la 2 =
5) xy - x - y +1 =
6) 9xy + 3x - 3y - 1=
7) 25 x la 2 - 49 =
8) (x - 2) la 2 - 4 x la 2. =
9)x la 2 + 6x +9-y la 2 =
10)x la 2 + 7 x +6 =
11) x la 2 - 5x +6=
12)x la 2 + 2x - 3=
13) 2x la 2+x - 1=
14) x la 3 + x la 2 - 16x - 16=
Dau coroana!!


Răspuns :

1) x la 2 - 5x =x(x-5)
2) 3x la 10 + 9x la 8 =3xla8(xla2+3)
3) x(x + 1) - x - 1 =(x+1)(x-1)
4) x la 2 (x+1) + x (x+1) la 2 =x(x+1)(2x+1)
5) xy - x - y +1 =x(y-1)-(y-1)=(x-1)(y-1)
6) 9xy + 3x - 3y - 1=3x(3y+1)-(3y+1)=(3y+1)(3x-1)
7) 25 x la 2 - 49 =(5x-7)(5x+7)
8) (x - 2) la 2 - 4 x la 2. =(x-2-2x)(x-2+2x)
9)x la 2 + 6x +9-y la 2 =(x+3) la 2 - y la 2=(x+3-y)(x+3+y)
10)x la 2 + 7 x +6 =(x+6)(x+1)
11) x la 2 - 5x +6=(x-2)(x-3)